Roles of Asiatic Mindshare Ltd. on the impact of social media marketing by ACI Pure Foods on brand awareness and customer loyalty in Bangladesh - Mamud, Dewan Seam (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.